Advances and challenges of emotional education in higher education: A documentary review - Bracamontes Ceballos, Edith; Jiménez Macías, Iván Ulianov; Vázquez González, Guillermo César (IE Revista de Investigación Educativa de la REDIECH, 2024)
The relationship between emotions and cognitive processes has positioned emotional education as a relevant topic in the educational field; however, to achieve its full integration in higher education, it is imperative to know its current status. The objective of the study is to identify the main theoretical and empirical findings related to emotional education in higher education, emotional education in the teaching-learning process, and the training of university teachers in emotional education. To this end, a documentary review was carried out with a qualitative and descriptive approach, using repositories and scientific databases. Articles in Spanish and English published in Mexico and abroad were included, between 2017 and 2022. 67 documents were reviewed and 22 were selected and organized into three categories: a) emotional education in higher education, b) emotional education in the process teaching-learning, and c) teacher training in emotional education. The main findings show that emotional education has a positive influence on academic performance and the generation of favorable environments in the classroom, but also the urgent need for teacher training and facing challenges for its incorporation into the curriculum and educational processes, due to the scarcity of empirical studies related to its impact at the university level.